Methodology for self-report of rest pain (or spontaneous pain) vs evoked pain in chronic neuropathic conditions: a prospective observational pilot study - He, David (Pain Rep, 2017)
INTRODUCTION: The distinction between pain at rest and pain evoked by touch or movement has important clinical implications and may be associated with different mechanisms. However, current methods of clinical pain assessment pay little attention to directly distinguishing between these contrasting components of symptom burden. OBJECTIVES: We developed the 10-item “Functional Impact of Neuropathic Evoked and Spontaneous Symptom Evaluation” questionnaire designed to distinguish between rest and evoked pain. METHODS: A prospective observational pilot study of this questionnaire was conducted in 78 participants with neuropathic pain diagnoses. Other study measures included the self-report version of the Leeds Assessment of Neuropathic Symptoms and Signs questionnaire and a modified Brief Pain Inventory. Exploratory analyses were conducted to evaluate the validity of the Functional Impact of Neuropathic Evoked and Spontaneous Symptom Evaluation questionnaire. RESULTS: Pain symptoms often/very often/always (1) evoked by touch or movement, and (2) occurring at rest without tactile stimulation were reported by 81% and 65%, respectively. Evoked pain was associated with walking (64%) and standing (35%); and rest pain was associated with watching television (47%), reading (37%), and sitting (36%). Participants reporting both rest and evoked pain tended to report higher levels of pain interference compared to those reporting evoked pain only. DISCUSSION: These results provide support for the feasibility and validity of new patient-report methods to distinguish between rest pain and evoked pain in chronic neuropathic conditions. Future studies are needed to confirm the reliability and validity of these methods, which may facilitate important improvements in the research and development of new treatments for chronic pain.